2018
DOI: 10.1093/pcp/pcy179
|View full text |Cite
|
Sign up to set email alerts
|

ROC75 is an Attenuator for the Circadian Clock that Controls LHCSR3 Expression

Abstract: Strong light intensity leads to harmful overexcitation of the photosystems in green algae. In Chlamydomonas reinhardtii, LHCSR3 is required for the rapid protective response known as energy-dependent quenching (qE). Because the majority of photoacclimation analysis has been conducted under controlled laboratory conditions, physiological responses to natural environmental changes such as light/dark cycles have not been examined in detail. Regarding fitness in higher plants and microalgae, light-dark cycles repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…4 ). In addition, two previously reported regulators of qE, ROC75 28 and CrCO 26, 27 , are also included in this list of PHOT-dependent regulators. These observations are in line with an existing hypothesis 24 suggesting that a CUL4-dependent E3-ligase targeting CrCO, 26 acts downstream of PHOT.…”
Section: Resultsmentioning
confidence: 99%
“…4 ). In addition, two previously reported regulators of qE, ROC75 28 and CrCO 26, 27 , are also included in this list of PHOT-dependent regulators. These observations are in line with an existing hypothesis 24 suggesting that a CUL4-dependent E3-ligase targeting CrCO, 26 acts downstream of PHOT.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence to support that algal ancestors utilize circadian-regulated mechanisms to respond to abiotic stress. The C. reinhardtii clock is postulated to regulate photoprotection against harmful photosystem overexcitation from strong red light via the ROC75-mediated regulation of photoprotective effector genes like LIGHT-HARVESTING COMPLEX STRESS-RELATED3 (LHCSR3) (Kamrani et al, 2018). P. patens and the latest streptophyte algae (Zygnematales, Coleochaetales, and Charales) that diverged from land plants are also postulated to rely on LHCSRs for photoprotection (Gerotto & Morosinotto, 2013;Pinnola, 2019), though whether they are circadianregulated as CrLHCSR3 is unknown.…”
Section: Accepted Articlementioning
confidence: 99%
“…(LHCSR3) (Kamrani et al, 2018). P. patens and the latest streptophyte algae (Zygnematales, Coleochaetales and Charales) that diverged from land plants are also postulated to rely on LHCSRs for photoprotection (Gerotto & Morosinotto, 2013;Pinnola, 2019), although whether they are circadian-regulated as CrLHCSR3 is unknown.…”
Section: Eudicotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Cr pCRY knockdown line exerts a significantly lengthened period of about 27.9h compared to wild type (24.5h in average); it becomes arrhythmic after a few days under free-running conditions that are used to analyze clock properties. It was also suggested that pCRY positively regulates the clock component, ROC75, a putative transcription factor ( Kamrani et al, 2018 ). These data support the model that Cr pCRY is not only involved in circadian input but is also linked to the central oscillator.…”
Section: Variety Of Algal Cryptochromesmentioning
confidence: 99%